FEATURES OF THE RECEPTORS EXPRESSION FOR INTERLEUKIN 4 AND 5 IN THE FORMATION OF THE ATOPIC STATUS IN NEWBORNS - T.V. Turti; E.L. Semikina; L.S. Namazova-Baranova (Union of pediatricians of Russia, 2011)
Identification of the early markers of the onset of atopic march in children remains important for the effective primary and secondary prevention of allergic diseases. The article contains results of the study of the expression of receptors for interleukin of Th2 profile (IL 4, IL 5) in infants with the formation of the atopic status. The obtained results indicate that expression of receptors is different in families with burden atopic anamnesis and/or in case of impact of certain perinatal factors.Key words: newborn, atopy, interleukin receptors, CD124, CD125, immunoglobulin E.